Shoreline dynamics over last three decades and predictions for 2032 and 2042: a spatial analysis along the coastal stretch of Aruvi Aru and Kal Aru estuaries in Mannar district, Sri Lanka - Nadarajapillai Thasarathan; Lam Kuok Choy; Kadaruddin Bin Aiyub (Journal of Maps)
The North-Western coastal stretch of the Aruvi Aru and Kal Aru estuaries in Sri Lanka's Mannar district faces increasing vulnerability due to coastal erosion, but comprehensive research has been lacking until now. This study aims to analyze shoreline changes from 1988 to 2022 and forecast future changes until 2042. Landsat satellite images and statistical parameters such as LRR and AoR were used to calculate erosion and accretion rates. The maximum erosion rate was −4.7 to −5.3 m/year, while accretion ranged from 9.6 to 10.3 m/year. The Kalman filter model predicted further erosion in Vankalai West (45 m by 2042) and accretion in Pathaikaddumunai (78 m by 2042). Certain areas, including Vankalai, Naruvilikulam, and Kondachchikudah, were identified as high-risk zones prone to erosion. The study suggests implementing this technique for comprehensive coastal management strategies in Sri Lanka.